2018
DOI: 10.3390/toxins10090344
|View full text |Cite
|
Sign up to set email alerts
|

Effective Adsorption of Patulin from Apple Juice by Using Non-Cytotoxic Heat-Inactivated Cells and Spores of Alicyclobacillus Strains

Abstract: Patulin (PAT) is a major threat to many food products, especially apple and apple products, causing human health risks and economic losses. The aim of this study was to remove PAT from apple juice by using the heat-inactivated (HI) cells and spores of seven Alicyclobacillus strains under controlled conditions. The HI cells and spores of seven strains adsorbed PAT effectively, and the HI cells and spores of Alicyclobacillus acidocaldarius DSM 451 (A51) showed maximum PAT adsorption capacity of up to 12.6 μg/g b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…Several investigators showed that the binding between AFM1 and bacteria is partially reversible, suggesting the implication of non-covalent bonds such as hydrogen bonds and van der Waals interactions [104,105]. A potential clarification of this variation in the released amounts of AFM1 can be explained by the difference in the binding sites between strains or to cross-linked interactions between AFM1 molecules and different microbes [106]. It is noteworthy to mention that the stability of the formed AFM1/microbial complex remains crucial; thus, a stable complex ensures a safe excretion of mycotoxins from the human body [38,107].…”
Section: Effective Strategies For Afm1 Reductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several investigators showed that the binding between AFM1 and bacteria is partially reversible, suggesting the implication of non-covalent bonds such as hydrogen bonds and van der Waals interactions [104,105]. A potential clarification of this variation in the released amounts of AFM1 can be explained by the difference in the binding sites between strains or to cross-linked interactions between AFM1 molecules and different microbes [106]. It is noteworthy to mention that the stability of the formed AFM1/microbial complex remains crucial; thus, a stable complex ensures a safe excretion of mycotoxins from the human body [38,107].…”
Section: Effective Strategies For Afm1 Reductionmentioning
confidence: 99%
“…These inaccuracies are not only limited to the binding of AFM1 by microbial adsorbents but may extend to binding of different types of mycotoxins including aflatoxin B1, ochratoxin A, patulin, and other toxins following similar procedures [106,108,125,126].…”
Section: Effective Strategies For Afm1 Reductionmentioning
confidence: 99%
“…The reduction was statistically significant but much lower than the reduction caused by living cells, especially for C. lusitaniae and R. paludigenum. We assume that the removal of patulin from solution by heat-inactivated cells was caused by adsorption because many microorganisms [ 48 , 49 ], including yeast [ 50 , 51 ], reduce patulin concentration in solution by physical adsorption. The process is likely to be reversible, which further diminishes its attractiveness for applications.…”
Section: Discussionmentioning
confidence: 99%
“…The potential of lactic acid bacteria (LAB) in removing PAT from diverse food, notably apple and its derivatives, and the mechanism involved have been sufficiently investigated by many authors and believed to be competent, safe, and reliable for PAT adsorption and/or degradation from apple juice, with no detrimental effect on juice quality parameters [ 30 , 31 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ]. The appreciable benefits of L. casei , such as bad bacteria, mold growth, and tumor inhibition, in addition to lipid metabolism, antioxidant capacity, and immunity improvement, are well-known.…”
Section: Introductionmentioning
confidence: 99%
“…Initial PAT concentration, contact time, pH, and temperature addition to the adsorption mechanism of PAT were studied [ 17 , 24 , 46 , 47 ]. However, there are not enough citations showing the adsorption mechanism samples having different °Brix were provided, and the adsorption mechanism of PAT needs to be clearer [ 35 ].…”
Section: Introductionmentioning
confidence: 99%